Disulfidptosis: a new target for central nervous system disease therapy - Chang, Jing; Liu, Danhong; Xiao, Yuqi; Tan, Boyao; Deng, Jun; Mei, Zhigang; Liao, Jun (Frontiers in Neuroscience, 2025)
Disulfidptosis is a pathologic process that occurs under conditions of NADPH deficiency and excess disulfide bonds in cells that express high levels of SLC7A11. This process is caused by glucose deprivation-induced disulfide stress and was first described by cancer researchers. Oxidative stress is a hypothesized mechanism underlying diseases of the central nervous system (CNS), and disulfide stress is a specific type of oxidative stress. Proteins linked to disulfidptosis and metabolic pathways involved in disulfidptosis are significantly associated with diseases of the CNS (neurodegenerative disease, neurogliomas and ischemic stroke). However, the specific mechanism responsible for this correlation remains unknown. This review provides a comprehensive overview of the current knowledge regarding the origin elements, genetic factors, and signaling proteins involved in the pathogenesis of disulfidptosis. It demonstrates that the disruption of thiometabolism and disulfide stress play critical roles in CNS diseases, which are associated with the potential role of disulfidptosis. We also summarize disulfidptosis-related drugs and highlight potential therapeutic strategies for treating CNS diseases. Additionally, this paper suggests a testable hypothesis that might be a promising target for treating CNS diseases.